Acidolysis as a biorefinery approach to producing advanced bioenergy from macroalgal biomass: A state-of-the-art review. (December 2020) - Hong, Ying; Wu, Yi-Rui
Graphical abstract: Highlights: Various acids involved in the hydrolysis of macroalgal biomass are summarized. Combined pretreatment for the improved macroalgal hydrolysis is described. Conversion of acid-based macroalgal hydrolysate into advanced biofuels is reviewed. Challenges and trends for the future development of macroalgal biomass are discussed. Abstract: Facing fossil fuels consumption and its accompanying environmental pollution, macroalgae, as a major part of the third-generation (3G) biomass, has great potential for bioenergy development due to its species-abundant, renewable and carbohydrate-rich properties. Diluted acid treatment is one of the most effective approaches to releasing fermentable sugars from macroalgal biomass in a short period, but the optimal conditions need to be explored to maximize the hydrolytic yield for the subsequent microbial conversion. Therefore, this review aims to summarize the latest advances in various acids and other auxiliary methods adopted to increase the hydrolytic efficiency of macroalgae. Following an overview of the strategies of different algal types, methods involved in the bioconversion of biofuels and microbial fuel cells (MFC) from algal hydrolysates are also described. For the 3G biorefinery development, the review further discusses key challenges and trends for future utilizing marine biomass to achieve the large-scale industrial production.